Investigação criminal pelo Ministério Público: estado atual do debate no STF - Cavalcanti, Mariana da Costa Ribeiro (2014)
This study aims to provide a critical analysis about criminal investigation in Brazil, especially in regards to the possibility of the Department of Public Prosecution to directly perform it. Firstly, we tackle the history of penal procedure systems, focusing on the one which was adopted in Brazil and its connection with the institute of criminal investigation, particularly concerning to division of duties in the criminal prosecution. Secondly, we deeply assay the institute of criminal investigation, including its concept, history and regulation in brazilian legal system. Next, considering that the Constitution of the Brazilian Republic have not defined the function of criminal investigation as an exclusive task of Judicial Police, we discuss the main constitutional, subconstutional and doctrinaire tracks used to justify the legitimacy of criminal investigation carried out by the Department of Public Prosecution. After that, we carefully analyze the recent jurisprudential trend of the Supreme Federal Court about this topic. At last, we present proposed laws that intend to solve the matter definitely by regulating criminal investigation realized by Public Prosecution members.